Réponses

Meilleure réponse !
2013-08-20T17:36:02+02:00

                        B  =  (−3x + 4y) ÷ (5x − 3y)

 

 

1.   Avec   x  =  7

         et    y  =  8

     on a :

                        B  =  [−3(7) + 4(8)] ÷ [5(7) − 3(8)]

                            =  (− 21 + 32) ÷ (35 − 24)

                            =  11/11

                            =  1

 

 

2.   Avec   x  =  −2

         et    y  =  −7

     on a :
                        B  =  [−3(−2) + 4(−7)] ÷ [5(−2) − 3(−7)]

                            =  (6 − 28) ÷ (−10 + 21)

                            =  −22/11

                            =  −2